The Influence of School Principal Leadership, Work Team, and Work Motivation on Satisfaction Work Junior High School Teacher in Minahasa District - Parinsi, Mario Tulenan; Sumual, Tinneke E. M.; Maringka, Riviva W; Dondokambey, Clay J H; Paath, Deicy (International Journal of Information Technology and Education, 2024)
Teachers are dissatisfied with their colleagues or work teams at school. Objective research looks at the influence of principal leadership, work teams, and work motivation on the satisfaction of Work Teachers. Method study approaches quantitatively. Results study show There is an influence of direct leadership head school to motivation Work Teachers. There is influence direct leadership head school to satisfaction Work Teacher. There is influence leadership head schools indirectly affect job satisfaction through teacher work motivation. There is an influence team directly on teacher work motivation. There is a direct influence on the work team teacher job satisfaction. There is an indirect influence of work teams on teacher job satisfaction through work motivation. There is an influence of work motivation on teacher job satisfaction. The research conclusion is that there is a direct and indirect relationship between school principal leadership, work teams, and work motivation satisfaction among Work Teachers.